Analisis Pemahaman Mahasiswa Terhadap Keterampilan Dasar Komunikasi Konseling Pada Mata Kuliah Mikro Konseling - Sitti Rahmi; Suriata Suriata (ILIN Institute Makassar, 2019)
This research aimed: (1) to find out and describe the level of students' understanding towards basic counseling communication skills in micro counseling course, and (2) to propose one of alternatives in the plan for implementing service, thus students can understand and master the basic skills of counseling communication. This research was descriptive quantitative or survey research. Method of collecting data used was test and conducted by giving questionnaires and interviews. The results showed that in measuring the basic skills of counseling communication, there were 30 subjects (97%) with good categories, 1 subject (3%) with sufficient categories. It can be explained that overall the basic skills of student counseling communication are good, only 1 subject who has sufficient skills.